REDE SOCIAL INFORMAL E TRANSFERÊNCIA DE CONHECIMENTO TÉCNICO EM P&D - Ribeiro, Lourdes Carniello (2012)
This essay goals to verify how the interpersonal relationships can contribute to an information and technical know-how sharing in a research centre of a public undertaking, organized in matrix structure, that develops basic engineering design to the oil and gas industry. Through the social network analysis (SNA) technique we reveal how the employees sample of the unit under study is organized, considering four factors: information, knowledge, friendship and trust. The theoretical background addressed the emergence of the SNA technique, main concepts and applicability in organizational environments as well the importance of human capital as a key gear of the information sharing in the Organizational Knowledge Management. The research is characterized like a case study; based on the information got from the questionnaire given to the sample, and, with the UCINET and NETDRAW tools, it was possible to identify the main actors, the relationship between them and how they are organized. Thus, we can verify bottlenecks in the information and knowledge sharing as well little interaction between the groups of the management that was studied.